Variables associated with gestational anxiety in primigravidas and multigravidas - De Almeida Schiavo, Rafaela; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Perosa, Gimol Benzaquen [UNESP] (Associacao Brasileira de Psicologia, 2018)
This study aimed to describe and compare anxiety on primigravidae and multiparous in the third quarter, as well as to identify, among sociodemographic variables and of pregnancy, which ones were associated with high anxiety. There were 479 pregnant women participants who responded to an anxiety instrument (STAI) and a questionnaire on sociodemographic variables and about pregnancy. The groups were statistically compared e a logistic regression model was composed to evaluate associations. The results indicated that 36% of pregnant women presented symptoms of high anxiety on third gestational trimester, with a predominance of the multiparous in relation to the primigravidae. For the multiparous, the highest chance for high anxiety was associated with low income and for the primigravidae to the threat of miscarriage in early pregnancy. For both primigravidae and multiparous, wanting the baby appeared as a protective factor for high anxiety. The expressive percentage of pregnant women with anxiety symptoms justifies the offering of prevention services and promotion of mental health for pregnant women, with a differentiated attention to primigravidae and multiparous.
Keywords: Anxiety; Multiparous; Pregnant; Primigravidae